RACIAL DISCRIMINATION IN JORDAN PEELEâ€™S â€œGET OUTâ€ FILM (Sastra Inggris UNPAM, 2022)
The aim of this study was to describe the issues of racial discrimination found in Jordan Peelâ€™s Get Out film, released in 2017. This study used a qualitative method, and the data sources were taken from the scene and dialogues of the film. The theories of racial discrimination from Giddens (2006) and Haney-Lopez (1994) were applied in this study. The result of this study showed racial discrimination not only happens verbally but also by act or even more scary. Racial discrimination can be done by an individual or by a group. Group of the majority will limit the freedom of the minority. If the other African American cannot struggle to stop the discrimination, the other one can start the meaningful action to change. Everyone has the same right and freedom in every country; like the meaning in the title of the film Get Out, people have to fight and get out from the discrimination they experience. Keywords: cinematography, racial discrimination, struggle.